Sistem pendidikan di pondok pesantren RU Sakatiga dalam perspektif nilai-nilai pendidikan multikultural - Mulyani, Sri; Afriantoni; Afgani, Muhammad Win (Program Studi Magister Pendidikan Agama Islam, 2024)
Indonesian society is a society with a very complex level of diversity, a society with this diversity is known as a multicultural society. In the diversity of Indonesian society, education regarding multicultural education is very necessary. The content of multicultural educational values at the Raudhatul Ulum Islamic Boarding School includes the Raudhatul Ulum Islamic Boarding School having the principle of